The relationship between different facets of empathy, pain perception and compassion fatigue among physicians - Gleichgerrcht, Ezequiel; Decety, Jean (Frontiers in Behavioral Neuroscience, 2014)
Background: Medical practitioners such as physicians are continuously exposed to the suffering and the distress of patients. Understanding the way pain perception relates to empathetic dispositions and professional quality of life can contribute to the development of strategies aimed at protecting health professionals from burnout and compassion fatigue. In the present study we investigate the way individual dispositions relate to behavioral measures of pain sensitivity, empathy, and professional quality of life. Methods: A secure Web-based series of self-report measures and a behavioral task were administered to 1,199 board-certified physicians. Additionally, surveys were used to obtain measures of demographic and professional background; dispositional empathy (empathic concern, personal distress, and perspective taking); positive (compassion satisfaction) and negative (burnout and secondary traumatic stress) aspects of their professional life. In the behavioral task, participants were asked to watch a series of video clips of patients experiencing different levels of pain and provide ratings of pain intensity and induced personal distress. Results: Perceived pain intensity was significantly lower among more experienced physicians but similar across specialty fields with varying demands of personal stress. Perceiving videos of patients in pain, however, elicited more personal distress among physicians in highly demanding medical fields, despite comparable empathy dispositions with other fields. The pain of male patients was perceived as less intense than the pain of female patients, and this effect was more marked for female physicians. The effect of dispositional empathy on pain perception and induced personal distress was different for each sub-component, with perspective taking and empathic concern being predictive of the behavioral outcomes. Physicians who experience both compassion satisfaction and fatigue perceive more pain and suffer more personal distr